(untitled) (Research, Society and Development, 2021)
Celiac disease is a chronic enteropathy and immune-mediated of the small intestine that affects about 1.1% to 1.7% of the world population. Presently the effective medical treatment is the restriction of gluten-containing foods. However, economic cost and nutritional quality have negatively influenced the maintenance of a gluten-free diet in several countries by consumers. In Brazil, the scarcity of information on the economic cost and nutritional quality of these products points to the need for incursions on the topic. In order that compile this information, we accomplish a cross-sectional study through a comparative analysis between the economic costs and nutritional information of products targeted at consumers with celiac disease available on an e-commerce platform in Brazil. The study revealed that in Brazil, products with gluten have higher energy value, carbohydrate content, total fats, saturated fat, protein and fiber when compared to their gluten-free versions, while these had a higher economic cost. We evidenced the need for the development of new products with ingredients that add nutritional value without encumber the final cost to the consumer with celiac disease.